Coping the discrepancy between moral and intellectual achievement: the model integration of higher education and modern Islamic Boarding Schools in Indonesia. - Arroisi, Jarman; Mustopa, Rodhi Hakiki Bin Cecep; Djayusman, Royyan Ramdhani (Indonesian Journal of Islam and Muslim Societies, 2025)
Currently, higher education institutions in Indonesia are considered to produce products that emphasize the intellectual aspect but lack the moral element. Meanwhile, it is recognized that pesantren institutions’ products emphasize the moral aspect but lack the intellectual element. This paper aims to analyze the model integration of higher education with modern Islamic Boarding Schools, the system of instilling values, the philosophy of the Islamic boarding school, and strategies for facing challenges—a case study of Darussalam University (UNIDA) Gontor. In addition to using the participatory observation method as a data collection tool, this paper uses descriptive analysis during reading, discussing, and writing. With this method, three important findings can be conveyed; first, the integration model between UNIDA Gontor and modern Islamic boarding schools can be appropriately implemented if an adequate boarding system supports it. Second, a boarding system that emphasizes discipline and offers a dense curriculum and a range of extracurricular activities can effectively instill values, work ethics, and the philosophy of the Islamic boarding school while also embodying the triharma of higher education. Third, the power of motivation, support from various parties, and the active participation of students in the educational process will determine their achievements and competencies while on campus or in society.